2011
DOI: 10.1080/15257770.2011.611483
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Tests for Primary Renal Hypouricemia

Abstract: Primary renal hypouricemia is a genetic disorder characterized by defective renal uric acid (UA) reabsorption with complications such as nephrolithiasis and exercise-induced acute renal failure. The known causes are: defects in the SLC22A12 gene, encoding the human urate transporter 1 (hURAT1), and also impairment of voltage urate transporter (URATv1), encoded by SLC2A9 (GLUT9) gene. Diagnosis is based on hypouricemia (<119 μmol/L) and increased fractional excretion of UA (>10%). To date, the cases with mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Recent studies have suggested that RHUC is not necessarily restricted to East Asian populations, as previously thought. Loss-of-function mutations affecting URAT1 have also been found in Caucasian populations in Macedonia, the United Kingdom, and the Czech Republic [4,5,10,11]. Additionally, case reports from European patients with symptoms of RHUC have also been previously reported [12,13].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have suggested that RHUC is not necessarily restricted to East Asian populations, as previously thought. Loss-of-function mutations affecting URAT1 have also been found in Caucasian populations in Macedonia, the United Kingdom, and the Czech Republic [4,5,10,11]. Additionally, case reports from European patients with symptoms of RHUC have also been previously reported [12,13].…”
Section: Discussionmentioning
confidence: 91%
“…We recently identified and functionally characterized three novel variants in the SLC22A12 gene in Czech RHUC patients [4][5][6]. Our findings of two c.1245_1253del heterozygous individuals in a control cohort of 109 subjects from the Roma population suggested the existence of prevalent variant in this minority population in the Czech Republic.…”
Section: Introductionmentioning
confidence: 77%
“…The first urate transporter described was SLC22A12/URAT1 1 . Mutations in the SLC22A12/URAT1 gene have been associated to primary renal hypouricemia type I (OMIN 220150) in several populations 1,2,3,4,5 , although some ethnic differences may explain the lack of association between this gene and primary renal hypouricemia in other populations such as Greek whites 6 . Because this transporter reabsorbs urate from the renal tubule, loss of function mutations may cause renal urate wasting and hypouricemia.…”
Section: To the Editormentioning
confidence: 99%
“…Confirmation of the diagnosis is accomplished by molecular analysis of the SCL22A12 and SLC2A9 genes. [31][32][33] Therapy is based on alkalization of urine, increased fluid intake, and avoidance of strenuous exercise. 29 For patients in whom no mutation has been found, referral to an academic medical center will help further research in this disorder and provide useful information for affected families.…”
Section: Primary Hereditary Renal Hypouricemiamentioning
confidence: 99%